OPTIMALISASI EDUKASI MPASI UNTUK MENINGKATKAN PENGETAHUAN ORANG TUA BALITA DI PERKAMPUNGAN ADAT NAGARI SIJUNJUNG - Riska Oktaviana; Ira Nurmala; Rery Afianto; Muh Arfah; Erfandi Pratama; Rahma Rizki Nabila (As-Sidanah, 2025)
Malnutrition remains a major issue for infants and children under five years old. Stunting is one of nutrition problems among children in Indonesia and continues to be a focal point in health concerns. The 2023 Indonesian Health Survey (SKI) indicates that approximately 1 in 5 children aged 0-59 months in Indonesia suffer from stunting. The aim of this community service is to provide health education to enhance mothers' knowledge and skills in preparing Complementary Feeding (MPASI) and to raise awareness about the long-term impacts of stunting in the Nagari Sijunjung Traditional Village. The results of the pre-test and post-test measuring mothers' knowledge of MPASI showed that the highest percentage of knowledge before the intervention was in the sufficient category, while after the intervention, it improved to the good category. There was a notable increase in the percentage of mothers with good knowledge after receiving educational interventions through counseling and cooking demonstrations. In conclusion, counseling and cooking demonstrations on MPASI can improve mothers' knowledge about MPASI, and it is recommended that health workers optimize mothers' knowledge by conducting repeated face-to-face sessions.